LANGUAGE DESCRIPTION (GRAMMAR): FUN WAY TO LEARN GRAMMAR USING NUMBER ONE FOR ME SONG BY MAHER ZAIN - Miranti, Ririt Rachma; Oliviera, Briliant (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Learning English using song is one of fun way that has been replaced into the school syllabus at Junior High School and Senior High School for 2013 curriculum. This study aimed to approach and reinforce grammar using song of Maher Zain in title Number One for Me by analysing the terms of grammar from its lyric. The focus of this study is about grammar which include: present tense, past tense, future tense, phrasal verb, noun phrase, gerund and the grammatical errors. Engaging lessons with model song will motivate students to learn grammar interestingly. The researcher conclude, if the terms of grammar in Maher Zain?s song has different kind and it is interesting to be learn. His songs always contain deep advices and this song tells about the love of mothers to their children and the children feel to their mothers.